Prenatal Immunization to Prevent Viral Disease Outcomes During Pregnancy and Early Life - Goswami, Ria; Pavon, Carolina Garrido; Miller, Itzayana G.; Berendam, Stella J.; Williams, Caitlin A.; Rosenthal, Danielle; Gross, Mackensie; Phan, Caroline; Byrd, Alliyah; Pollara, Justin; Permar, Sallie R.; Fouda, Genevieve G. (Frontiers in Virology, 2022)
Pregnancy significantly elevates the risk of developing severe viral diseases, which can have a detrimental effect on fetal development and increases maternal mortality. In addition, certain viruses can be transmitted vertically from mother to babies, either in utero, during delivery, or postnatally during breastfeeding, resulting in congenital or neonatal diseases and associated sequelae. While neonates are highly susceptible to viral infections and severe disease outcomes, due to the immaturity of their developing immune system, virus-specific maternal antibodies transferred either trans-placentally or via breast milk provide protection to infants during the first months of life. Thus, maternal prenatal immunization is important not only to protect pregnant women from viral diseases, but also to prevent infection and/or improve disease outcomes for the fetuses and neonates via passively transferred antibodies. In this review, we discuss the protective role of maternal antibodies against three categories of viruses: (i) viruses that cause severe maternal disease outcomes with mainly indirect consequences to the fetus (e.g. SARS-CoV-2, influenza, DENV, filovirus), (ii) those that are vertically transmitted from mother to their infants and cause congenital diseases (e.g. HIV, ZIKV and CMV), and (iii) those that cause elevated disease severity among neonates and infants postnatally (e.g. RSV, Rotavirus, Norovirus, HSV and HBV). Furthermore, we review relevant pre-clinical animal models that can be employed to develop novel immunization strategies against these viruses to enhance protection of pregnant women and their babies.